Peluang dan Tantangan dalam Efisiensi Anggaran Negara pada Transformasi Digital Pelayanan Publik - Jelita Silvia Hutabarat; Junita Mawartina; Dewi Yanti; W Pangestoeti (Konstitusi : Jurnal Hukum, Administrasi Publik, dan Ilmu Komunikasi, 2025)
Digital transformation is one of the main instruments in bureaucratic reform efforts aimed at improving the quality of public services and state budget efficiency. Through the application of information technology such as e-government, e-budgeting, and digitalization of public services, the government can reduce operational costs, accelerate administrative processes, and increase transparency. However, in practice, this transformation process faces various challenges, such as infrastructure gaps, low digital literacy, internal resistance, and data security threats. This study aims to identify opportunities and challenges for digital transformation in the context of state budget efficiency in Indonesia. The method used is a literature study with a descriptive-qualitative approach. The results of the analysis show that digital transformation plays an important role in driving fiscal efficiency, but requires strong policy support, increased human resource capacity, and equitable digital infrastructure development.